Development of a miniature vapor compression refrigeration system for electronic cooling - Davies, G; Eames, I; Bailey, P; Dadd, M; Janiszewski, A; Stone, C; Maidment, G; Agnew, B (2010)
Computer chips have generally been cooled by means of a heat sink/fan device; however, such systems are now approaching their limits and in future alternative techniques/devices will be needed. A 3-year project, involving collaboration between groups at three UK universities, is being undertaken to develop a miniature refrigeration device for the cooling of future microprocessors and electronic systems. Using conventional vapor compression refrigeration technology for the cooling of small computer packages has generally resulted in low heat fluxes, however, microchannel devices have shown heat transfer coefficients up to 16 times greater, and porous medium channels even higher heat transfer rates. Porous media heat exchangers are being developed by Newcastle University and some results from this work are reported here. Surface contamination by lubricating oil from the compressor often causes problems with small passage heat exchangers. Oxford University's Cryogenics Group have developed specialised oil-free compressors for low temperature cooling systems for space applications. Such a compressor is being adapted for use in the miniature vapor compression refrigeration device. The paper discusses development work on the compressor design. Conventional size refrigeration systems have sufficient capacity to dampen out transient behaviour resulting from variations in local temperatures and flow rates, but this is not the case for miniature systems. Based on earlier work at London South Bank University, a model has been developed to study transient behaviour in miniature refrigeration systems. The basis of the mathematical model is explained within the paper, as well as providing provisional results from the simulations. The paper identifies the potential need for computer cooling and highlights the opportunity to develop specific cooling solutions. Previous relevant work in this area is also highlighted. The paper provides details of novel work being carried out on modelling, micro-heat transfer and compressor development. Copyright © 2009 by ASME.